Slides to Philosophy 167: Class 7 -- Galileo's Two New Sciences: Projectile Motion -- Part 7. - Smith, George E. (George Edwin), 1938- (Tufts Archival Research Center, 2015)
Generally corresponds to the video segment: Class 7, Part 7.